Paleo‐Terrain Research: Finding the First Settlement Sites of Remote Oceania. Issue 3 (30th December 2013) - Carson, Mike T.; Buvit, Ian; Carson, Mike T.
<x xml:space="preserve">Abstract</x> A paleo‐terrain approach can situate ancient sites within their original landscape settings, as illustrated in a case study of the Mariana Islands in the western Pacific. This example combines computer‐aided terrain modeling with site‐specific excavations to reconstruct the shapes and configurations of landforms during the period of first human settlement of Remote Oceania, 1500–1000 B.C. The results support new understanding of humanity's first contact with the Remote Oceanic environment. The same approach can be applied in other settings to advance programs of site‐discovery and general studies of ancient site settings and ecology.